2020
DOI: 10.3389/fpls.2020.00237
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Production of Biopharmaceutical and Biotherapeutic Proteins

Abstract: Efforts to express human therapeutic proteins in photosynthetic organisms have been described in the literature. Regarding microalgae, most of the research entailed a heterologous transformation of the chloroplast, but transformant cells failed to accumulate the desired recombinant proteins in high quantity. The present work provides methods and DNA construct formulations for over-expressing in photosynthetic cyanobacteria, at the protein level, human-origin bio-pharmaceutical and bio-therapeutic proteins. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…TEV. 20,22,27 In this case, the nptI gene itself was chosen as a leader sequence in the fusion construct, since it was shown to enhance the heterologous protein expression in cyanobacteria while, at the same time, acting as a selectable marker. 27 To this aim, fusion construct nptI*TEV (Figure 1C) was designed to replace the psbA2 gene in the respective locus.…”
Section: Development and Application Of The Tobacco Etchmentioning
confidence: 99%
See 3 more Smart Citations
“…TEV. 20,22,27 In this case, the nptI gene itself was chosen as a leader sequence in the fusion construct, since it was shown to enhance the heterologous protein expression in cyanobacteria while, at the same time, acting as a selectable marker. 27 To this aim, fusion construct nptI*TEV (Figure 1C) was designed to replace the psbA2 gene in the respective locus.…”
Section: Development and Application Of The Tobacco Etchmentioning
confidence: 99%
“…Recent work from this lab showed that IFN, as a CpcB*IFN fusion construct, could accumulate in transformant cyanobacteria to about 12% of the total cellular protein. 20 However, it was not clear whether cleaved IFN from a CpcB*IFN fusion construct could be stable in the cyanobacterial cytosol. To address this question, the cpcB*IFN construct 20 was modified to install the cleavage tev sequence immediately prior to the IFN-encoding DNA (Figure 8A).…”
Section: Development and Application Of The Tobacco Etchmentioning
confidence: 99%
See 2 more Smart Citations
“…Biocontainment can be improved further by codon reassignment of the transgenes in the chloroplast [119]. Taken together, barriers encountered in the use of plantbased systems to produce recombinant protein or other heterologous products would make them less attractive than photosynthetic microorganisms, for example, microalgae and cyanobacteria [29]. More than 100 foreign or native proteins have thus far been produced in algal chloroplasts, including 40 different therapeutic proteins produced in C. reinhardtii chloroplasts [183].…”
Section: From Nucleus To Organelle Engineeringmentioning
confidence: 99%